CHARACTERISTICS OF DYSLIPIDEMIA AMONG HYPERTENSIVE PATIENTS ATTENDING AND TREATED AT TRA VINH GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of dyslipidemia among hypertensive patients attending the Tra Vinh General Hospital in 2024.Subjects and methods: A descriptive cross-sectional study was conducted on 163 hypertensive patients. Dyslipidemia was defined according to the Vietnamese Ministry of Health’s Guidelines for the diagnosis and treatment of endocrine and metabolic diseases. The analysis focused on the overall prevalence of dyslipidemia, the number of abnormal lipid components, and the characteristics of individual lipid parameters, including non-HDL-C.Results: The prevalence of dyslipidemia was 84.1%. Elevated LDL-C was the most common abnormality (69.9%), followed by elevated triglycerides (57.7%) and elevated total cholesterol (51.5%). Reduced HDL-C was observed in 19.6% of patients. Combined lipid abnormalities involving two or more components accounted for 66.8% of cases, with three-component dyslipidemia being the most frequent pattern (36.8%). Elevated non-HDL-C was identified in 73.7% of patients with dyslipidemia.Conclusion: Dyslipidemia is highly prevalent among hypertensive patients at Tra Vinh General Hospital, predominantly in the form of combined lipid abnormalities. Elevated LDL-C represents the most frequent disorder. The high proportion of elevated non-HDL-C suggests a substantial atherogenic burden in this population.
Keywords: Hypertension, dyslipidemia, LDL-C, HDL-C, non-HDL-C.